The Influence of Economic Literacy Proficiency and Financial Literacy on Business Performance in Micro, Small, and Medium Enterprises (MSMEs) in the Hanggar Talasalapang Area, Makassar - Indriana; Ramli, Muh.; Marsuni, Nur Sandi; Ismawati, Ismawati (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Micro, Small and Medium Enterprises (MSMEs) are one of the driving sectors of the Indonesian economy, including in Makassar City. The development of MSMEs is a priority in Makassar's economic development. Especially in Makassar, there is an area called the Talasalapang Hangar area, which houses MSME clusters that focus on culinary tourism, offering a variety of food and drinks. This research will be carried out in the Talasalapang Hangar Area of Makassar City with an implementation time of 12 months. The population in this study of all MSMEs in the Talasalapang Hangar Area amounted to 155 MSMEs, sampling was carried out using purposive random sampling techniques. The minimum number of samples is 112 MSMEs in the Talasalapang Hangar area of Makassar City. For research data collection instruments using questionnaires in obtaining quantitative data. So in this study it is concluded that: 1) the picture of economic literacy in MSMEs in the Talasalapang Hangar area is generally categorized as low, the picture of financial literacy in MSMEs in the Talasalapang Hangar area is generally categorized as high and the picture of business performance in MSMEs in the Talasalapang Hangar area is generally categorized as low. 2) there is an influence of economic literacy and financial literacy together on business performance in MSMEs in the Talasalapang Hangar area, the magnitude of the influence together is 42%. 3) there is a positive and significant influence of economic literacy on business performance in MSMEs in the Talasalapang Hangar area, and 4) there is a positive and significant influence of financial literacy on business performance in MSMEs in the Talasalapang Hangar area.